Modelling the Effective Factors on Temporal and Thermal Island Distribution of Qom applying Tasseled Cap Transformation (TCP) - Hossein Ghiasvand Nanji; Behnam Tashayo; Mehdi Momeni; Homayoun Yazdanpanah (جغرافیا و پایداری محیط)
Urban heat islands in hot and dry climates have adverse effects on the environment and human health. In this study, a method has been proposed to investigate the factors affecting the heat islands of Iran's central plateau climate. In the first step, after applying geometric, radiometric, atmospheric corrections and preparing Landsat 8 satellite images, including OLI-TIRS sensors, Tasseled Cap transformation is created. In the second step, the surface temperature of the earth is extracted using Split window algorithm. In the third step, in order to evaluate the heat islands, the Urban Thermal Field Variance Index is classified into six levels. Finally, using the correlation coefficient between TCT and Urban Thermal Field Variance Index indicators, the relationship of heat islands with the desert, urban areas, vegetation, and humidity is evaluated. In order to evaluate the proposed method, the city of Qom has been studied. The results of the proposed method show that heat islands are inversely related to the amount of vegetation (-0.613), water and humidity (-0.535) and directly related to the amount of soil and desert areas (0.709). Examining the Urban Thermal Field Variance Index, it was shown that the rate of this index in the core of the studied city is less than the outskirts of the city which can be due to the expansion and dispersion of the city, insulation of the roofs of residential houses, increasing the density of vegetation in the suburbs, river crossing through the city center, the presence of barren areas, ring roads, factories and industrial towns in the suburbs cited. The results reveal that the proposed method is an efficient method to analyze the factors affecting the phenomenon of heat islands.